Introducing a Controlled Outdoor Environment Impacts Positively in Cat Welfare and Owner Concerns: The Use of a New Feline Welfare Assessment Tool - de Assis, Luciana Santos; Mills, Daniel Simon (Frontiers in Veterinary Science, 2021)
There is much debate over the pros and cons of allowing cats to roam freely as opposed to keeping them confined indoors. We surveyed owners who implemented a commercial physical containment system to the outdoors to evaluate their characteristics and the apparent impact of this system on cat welfare and owner perceptions. As part of the latter aim, we also developed a new feline welfare assessment tool based on the mathematical relationship between different measures. The survey was circulated to customers over the preceding 2 years of ProtectaPet® between May and June 2019 and gathered 446 responses. Univariate analyses compared changes following installation on factors such as the amount of time the cat spent outside, other cats entering the owner's garden and owners' concerns about their cat outside. Principal component analysis was used to reduce 21 potential indicators of feline welfare into fewer variables. This resulted in 4 subscales, 2 relating to positive welfare and 2 relating to negative welfare. The effects of installation of the containment system and significant predictors of these four welfare subscales were assessed. The majority of respondents lived in an urban environment with a relatively small garden, had multiple cats and a history of feline trauma associated with a road traffic accident. As expected, the time spent outside significantly increased, while the frequency of other cats entering the garden and owner concern about leaving their cats outside significantly decreased. The 4 welfare subscales grouped into positivity, maintenance behaviors, health issues and fearfulness; installation of the system was associated with significant improvements across all of these. Time spent outside after installation had a significant effect on positivity and, to a lesser extent, maintenance behaviors. Overall, installation was associated with positive changes in both owner and cat quality of life, which seem to be particularly associated with an increased sense of security. This suggests that housing cats within a controlled outside environment with physical barriers can provide a practical solution for many of the problems associated with cats being allowed out.